Caffeine gum and cycling performance: A timing study - Ryan, E. J.; Kim, C. -H.; Fickes, E. J.; Williamson, M.; Muller, M. D.; Barkley, J. E.; Gunstad, J.; Glickman, E. L. (The Journal of Strength and Conditioning Research, 2013)
The purpose of this study was to determine the most efficacious time to administer caffeine (CAF) in chewing gum to enhance cycling performance. Eight male cyclists participated in 5 separate laboratory sessions. During the first visit, the subjects underwent a graded exercise test to determine maximal oxygen consumption (VO2max). During the next 4 visits, 3 pieces of chewing gum were administered at 3 time points (120-minute precycling, 60-minute precycling, and 5-minute precycling). In 3 of the 4 visits, at 1 of the time points mentioned previously, 300 mg of CAF was administered. During the fourth visit, placebo gum was administered at all 3 time points. The experimental trials were defined as follows: trial A (-120), trial B (-60), trial C (-5), and trial D (Placebo). After baseline measurements, time allotted for gum administration, and a standard warm-up, the participants cycled at 75% VO2max for 15 minutes then completed a 7-kJ/kg cycling time trial. Data were analyzed using a repeated measures analysis of variance. Cycling performance was improved in trial C (-5), but not in trial A (-120) or trial B (-60), relative to trial D (Placebo). CAF administered in chewing gum enhanced cycling performance when administered immediately prior, but not when administered 1 or 2 hours before cycling.